Sistem Informasi Kerja Praktek dan Tugas Akhir Program Studi Sistem Komputer - Karlina Kusumaningrum; Adian Fatchur Rochim; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2013)
Information technology development today resulted in the growing number of internet users. Easy access of the internet makes it as a media presentation of data to both individuals and institutions. It is similar with Computer System major that has taken advantage of the Internet to provide a variety of information to both academic and community service in the field of information technology. But it is still using manual method to organize and inventory data associated with the On-Job Training (KP) and Final Project (TA) in a site. One way to ease the data organization is to design an information system that can record and organize all the data held by the Computer System. Design and Implementation phase begins with system requirement analysis. Its objection is to get a proper system specification. In design phase, Data Flow Diagram is used to represent data in a logic way. The result from design phase then implements with PHP programming language, associated with Database Management System MySQL, and Javascript to generate a dynamic web-based information system. The previous research “Perancangan Sistem Informasi Seminar dan Tugas Akhir Mahasiswa Jurusan Teknik Elektro Undip” was to organize database final project consist of schedule, seminar schedule, and test schedule. It used Unified Modeling Language (UML) consist of use case and activity diagram. The users of this information system were two, that were called admin and student. The result from information testing showed that all features like organizing students data, organizing teacher data, printing KP and TA data, uploading KP and TA data, alerting KP and TA coordinator about the schedule of the students worked well. The current research use Entity Relationship Diagram model system. This information system has five users, that are admin, student, teacher, KP coordinator, and TA coordinator.